The Dunny Comes in from the Cold - Humphris, Adrian; Mew, Geoff (Architectural History Aotearoa, 2025)
By the late nineteenth century, action was taken by local authorities in several major New Zealand cities and towns to instigate measures to improve sanitation to reduce or eliminate the spread of noxious diseases. Wellington led the way in 1898 by completing a citywide drainage system, to collect human waste from households and carry it to the sea at Moa Point on the south coast. The water closet was a necessary integral part of this system, with the attendant piping for odour dissemination. It was soon realised that the isolated external toilet or dunny situated well away from the main house, and a feature of the garden, was no longer necessary; instead, homeowners could have a special small room indoors to accommodate the toilet with its plumbing; hence the origin of "the smallest room in the house." An interim stage of house planning was to locate the toilet beneath a verandah overhang, possibly with an adjacent wash house or coal store. Or there might be a small add-on wing to the house with the same functions. Some toilets were in the same internal room as the bath, but this was generally uncommon. In this paper we look briefly at key features of the Wellington sanitation scheme, then analyse the number and locations of internal toilets using building permit plans for new houses. The changeover to internal toilets took many years, even decades in some areas, as they were difficult and costly to retrofit in older villas and some bungalows which had only recently got used to having piped water. Thus, the night cart system for collection and disposal of human waste from earth closets also had to continue - in some instances until the 1960s. Although the dunny was eventually replaced in towns and cities, it still lives on near huts in parks and reserves - but progress has generally led to better overall sanitation, and garden landscape design benefited accordingly.